Essential tort law for SQE1 - Laws, Wendy (New York: Routledge, 2022)
'Essential Tort Law for SQE 1 explains the key principles of tort law in a clear, easy-to-follow style. Principles are introduced and illustrated with reference to practical examples. The book demonstrates the skill of client case analysis, taking a clear and structured approach to analysing the facts of a client's case and then applying the relevant principles. It also includes a range of supportive features: Revision points: Each chapter concludes with a concise list of key revision points. Problem questions: To test understanding and analytical skills applied to practical scenarios. A companion website also provides suggested answers. Multiple choice questions: Each section of the book provides multiple choice questions following the SQE 1 question format (with answers to enable you to test your knowledge). Further multiple choice questions and answers are also provided on the companion website. The first in a series of books aimed at those preparing for SQE 1, this concise and accessible text provides a clear understanding of the tort element of SQE 1 and enables you to test your assessment skills'--
Introduction -- Harms, remedies, and client case analysis -- Trespass : land -- Trespass : person -- Negligence : duty of care -- Negligence : breach of duty -- Negligence : causation of damage and remoteness -- General defences -- Negligence : limited duty situations - economic loss -- Negligence : limited duty situations - psychiatric harm -- Remedies -- Employers' liability -- Vicarious liability -- Occupiers' liability : visitors -- Occupiers' liability : trespassers -- Product liability -- Private nuisance -- The rule in Rylands v Fletcher -- Public nuisance -- Defamation -- Misuse of private information -- Client case analysis skills in tort -- Key cases in tort law -- Problem questions -- Multiple choice question answers.
Includes bibliographical references and index. (307-311 pages)
Puan Shaizimah Badzri/ Ketua Perpustakaan Undang-Undang/ shai@ukm.edu.my/ 6393/ Pemilihan Ketua Perpustakaan Undang-Undang/ OC/ Bookline Services
Keywords: Torts -- England -- Examinations, questions, etc; Solicitors Qualifying Examination